Strategi Guru Pendidikan Agama Islam dalam Pembentukan Karakter Toleransi Beragama pada Peserta Didik - Gustina, Vera; Subhan, Subhan (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this research is to find out the strategies of Islamic religious education teachers in forming the character of religious tolerance in students. The type of research used is qualitative with data collection techniques including: observation, interviews, and documentation. The results of this study are the PAI teacher’s strategy in forming the character of religious tolerance in students at SD Negeri 101 Bengkulu City, namely at the discretion of the school principal by providing character education to teachers, especially Islamic education teachers and including material on the character of religious tolerance in the lesson plan by exemplary methods, habituation methods, advice methods, stories or story methods, methods of educating through discipline, methods of extracurricular activities based on Islam.